Oksidasi Protein Daging Merah dan Putih pada Ikan Tongkol Putih (Thunus Sp) oleh Sistim Katalis Logam CUSO./Ho. - Daniel A. N. Apituley; Zuheid Noor; Purnama Darmadji; Suparmo Suparmo (agriTECH, 2005)
properties of foodstuff including fish muscles, hence protein oxidation will provide significant effect the integrity of the foodstuff (fish muscles). The aims of this study were to examine the effect of metal–catalyzed oxidation concentration CuSO4 / H202 on the formation of carbOnyl protein, loss of protein solubility and protein denaturation in red and white meat of White Tuna (Thunus sp). The result indicated that the formation of carbonyl protein offish protein was influenced by types of meat and metal-catalyzed oxidation concentration CuSO4/H202. 1,02. The higher the concentration Cu504/ H20 ? the higher increased the carbonyl protein product in both white and red meat. Formation of carbonyl protein was also increased with the storage time. However, the increase of carbonyl protein of red meat is higher compare with the white meat. Counter post the existence of hidroxyl radical produced from metal-catalyzed oxidation apparently leads to the modification of secondary and tertiary structure of the protein, in turn affect to the protein solubility and protein denaturation. The percentage of loss of protein solubility in red and white meat were 28.74 – 45.31 % and 23.13 – 34.50 % respectively. While the percentage of the protein denaturation of red and white meat were 38.88 % and 32.00 % respectively.